2012
DOI: 10.1007/s10620-012-2184-6
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Expression of Toll-Like Receptors and Interleukins Are Increased in Both Children and Adult Celiac Patients

Abstract: TLR4 expression is associated with CD independently of age at diagnosis. Pediatric patients and adult patients have a similar inflammatory profile, making it possible to treat both with the same immunological therapy in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
0
19
1
Order By: Relevance
“…HC -healthy controls; rCD -recently-diagnosed celiac disease patients; CD-GFD -celiac disease patients on a gluten-free diet for more than one year; AU -arbitrary units multiplied by 10 3 or by 10 6 . of TLR7 observed in the present study may thus be related to recent viral infection. Eiro et al reported only a very low percentage of cases with positive immunostaining for TLR7 in biopsy samples from CD patients, and comparable TLR7 mRNA expression levels in duodenal tissues between CD patients and healthy controls [15]. Nonetheless, in contrast to the present study, those authors did not differentiate between newly-diagnosed and treated cases.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…HC -healthy controls; rCD -recently-diagnosed celiac disease patients; CD-GFD -celiac disease patients on a gluten-free diet for more than one year; AU -arbitrary units multiplied by 10 3 or by 10 6 . of TLR7 observed in the present study may thus be related to recent viral infection. Eiro et al reported only a very low percentage of cases with positive immunostaining for TLR7 in biopsy samples from CD patients, and comparable TLR7 mRNA expression levels in duodenal tissues between CD patients and healthy controls [15]. Nonetheless, in contrast to the present study, those authors did not differentiate between newly-diagnosed and treated cases.…”
Section: Discussioncontrasting
confidence: 92%
“…To date, the search for TLR2 and TLR4 expression in the small intestinal mucosa of celiac disease patients has resulted in inconsistent findings with respect to the type of change as well as disease status [6,15,16]. In peripheral blood, however, relevant data are missing.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms that cause the altered regulatory activity of T reg cells in CD, however, are not understood fully. As the active state of the disease has been associated with a proinflammatory Th17-driven response [25,26], we The effect of lactate (1 lg/ml) on FOXP3 isoforms expression was evaluated by real-time reverse transcription-polymerase chain reaction (RT-PCR) on PBMC from non-coeliac subjects (HC n 5 16) and coeliac patients (CD n 5 23) after a 48-h stimulation and normalized on 18S (a). Paired analysis was used to determine differences between the two isoforms' expression within each group of patients in both cultures conditions (b).…”
Section: Discussionmentioning
confidence: 99%
“…These cells are expanded in the small intestine of active coeliac patients and contribute to the pathogenesis of the disease not only by secreting proinflammatory cytokines, but also through cytolytic proteins such as perforin and granzymes [20,24]. Recently, Th17-associated cytokines have also been reported to be increased in the small intestinal mucosa of active CD patients [25][26][27], therefore suggesting a role of Th17 cells in the pathogenesis of CD. While deficiencies in the population of T reg cells have been associated with other autoimmune diseases such as systemic lupus erythematosus (SLE) [28], CD is characterized by an increased number of FoxP3 1 cells in the lamina propria of the small intestine [29,30].…”
Section: Regulatory T Cells (T Reg ) Represent a Subset Of Cd4mentioning
confidence: 99%
“…Dear Editor, We read with great interest the recent contribution by Eiró et al [1]. They reported that celiac disease (CD) patients with high levels of toll-like receptor 4 (TLR4) showed high levels of interleukins (IL-1, IL-6, IL-8, and IL-17) as well as transcription factors.…”
mentioning
confidence: 99%